Determining the Best Work Behaviour of the Laboratory Head Using The Technique For Order Of Preference By Similarity To The Ideal Solution - Evada Rustina; Hening Nakuloadi; Teguh Widodo; Nur Wening; Rianto Rianto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Vocational education is in high demand because it prepares students to be job-ready. In learning, it is more about work practices, internships, and in the laboratory than theory in class. Therefore, the existence of laboratories is essential in vocational schools. The research was conducted at the maritime school of SMK Putera Samodra, Yogyakarta, Indonesia, using the quantitative approach of the TOPSIS method to determine the best work behaviour performance from the head of the laboratory. Work behaviour assessment criteria include service orientation, integrity, commitment, discipline, and cooperation. According to the assessment results by the principal and 31 colleagues, the best work behaviour is that of the head of the merchant ship engineering laboratory. Overall, the best work behaviour analysis results can have a positive impact, such as recognition, improved leadership practices, and enhanced performance in all laboratories in vocational schools. Other potential implications of work behaviour research results for schools can be developing leadership with the best strategies, identifying areas for improvement, allocating more resources to laboratories, and the positive effects of leadership qualities on vocational schools.